PROCESSOS E FERRAMENTAS PARA O ACOMPANHAMENTO DE RESULTADOS PÓS- IMPLANTAÇÃO DE PROJETOS - Castro, Marcela Souto (2012)
This research aims at evaluating methodologies and practices in project management used in the market, by looking for gaps related to the monitoring of results subsequent to the implementation of projects, and by suggesting procedures, processes and practices that might improve the results in projects. Though post-project issues are normally dealt with by portfolio management, this study has proved that some project management practices and processes may be adopted by corporations on a project basis in a way to support post-project results. During the research, the related literature was reviewed, which pointed out factors for the post-project that might be transformed in better project management practices. Taking the aforementioned factors as a starting point, practice premises were raised and, later, tested through a survey applied to a public experienced in project management. That survey tested fourteen practice premises and measured the extent of their usage and how keen their perception was of the importance of those premises for the success of projects. According to the target public s perception, all the practices suggested would improve the post-project result, confirming the premise that such practices can actually increase the success of projects. The extent of usage, nevertheless, was regarded as lower than the importance of such practices, being this fact strongly proportional to the level of maturity in project management shown by the corporations where our volunteers worked. The answers to the survey were as well segmented in actors (sponsor, manager, or client), and type of project (internal or external to the corporation). Such segmentations showed relevant to the evaluation and use of the research premises. After the analysis of the survey, changes were suggested to the guide on best practices Project Management Body of Knowledge (PMBoK), which included, modified and detailed practices in project management.